Fragmentos inmanentes : introspección de mi casa (2017)
The human being is constantly redefined after the different points of rotation that travels throughout his life. In doing so, we are influenced by different systems of normalization that seek to shed our own judgment, persuade our way of behaving and implant the correct history of what we should be. But this is a journey that we should travel individually, along an introspective process that allows us to recognize our essence and thus achieve value. In this way we return to our childhood home, looking for our only point of reference in the world. Recognizing this place, as a space that has the power to shelter our thoughts and give us a moment of intimacy to listen to us, to observe and to reconnect with our inner self. However, we face that this place, as we lived in its time, has ceased to exist physically and now I intend to...